Bataan radio history an exploratory study on the birth and development of radio stations in Bataan - Cayanan, Jennelyn Joson, 1992- (2012)
"This study narrates and analyzes the interrelation of the various events and situation which led to the birth and development of radio as a mode of communication in Bataan. Using political economy of communication as its framework, the influences of the political, economic, social, cultural, and technological aspects on the birth, development, sustainability, and failure to survive of the radio stations in Bataan were examined. The period examined in this study begins from the pre-war up to the present Bataan radio, Archival research and semi-structured interviews were used to present the information proving the influence of environment, cultural practices, media, ownership, government and political intervention and financial capacity in the establishment and development of Bataan radio. This research also observed the rise of alternative radio to provide other media content aside from what is offered by the mainstream radio which has always been used to advance commercial and political gain and protect the interests of those who hold political and economic power."